1969
DOI: 10.1002/pol.1969.150070733
|View full text |Cite
|
Sign up to set email alerts
|

Silyl celluloses: A new class of soluble cellulose derivatives

Abstract: Two general methods for the silylation of cellulose have been developed. Silyl amides undergo silyl—proton exchange reactions with cellulose in polar solvents leading to displacement of 80–90% of the hydroxyl protons by silyl groups. The same products are obtained by reaction of the corresponding chlorosilanes with cellulose in pyridine; however, di‐ and trifunctional impurities present in commercial chlorosilanes have to be removed by scavenging with a carbohydrate in order to avoid crosslinking. Cellulose de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…These spectra confirm the structural changes produced by the etherification process when the OOH groups were substituted by OOSi(CH 3 ) is lower in the silylated compounds, compared with the corresponding band in cellulose spectrum. This decrease is proportional with the substitution degree, and can be used for a rather qualitative determination of the substitution degree.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…These spectra confirm the structural changes produced by the etherification process when the OOH groups were substituted by OOSi(CH 3 ) is lower in the silylated compounds, compared with the corresponding band in cellulose spectrum. This decrease is proportional with the substitution degree, and can be used for a rather qualitative determination of the substitution degree.…”
Section: Methodssupporting
confidence: 84%
“…The effects of polymer modifications by substitution with triorganosilyl groups (silylation) have been demonstrated 30 years ago; the increased solubility of silylated polymers in nonpolar solvents is particularly note worthy. [1][2][3] The silylcellulose derivatives have various uses; as fibers, 4 films, or liquid crystals, 5,6 a search in the literature revealed that rather a small number of studies are devoted to characterization of these compounds, especially in solution, a reduced number of studies are devoted to characterization of these compounds in solution. Most likely, this lack is perhaps determined both by synthesis difficulties and by the fact that in the absence of some peculiar measures of precaution, unstable products are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…6 Substitution of some hydroxyl protons causes drastic changes in the physical properties: in fact, silylated cellulose derivatives are often soluble in nonpolar solvents due to the significant reduction in the intermolecular hydrogen bonding. 7,8 For example, Wegner and co-workers 9,10 demonstrated that Langmuir monolayers of trimethylsilylcellulose ͑TMSC͒ could be transferred onto a hydrophobized substrate by the Langmuir-Blodgett ͑LB͒ method. Subsequent exposure to HCl vapor regenerated TMSC to pure cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Cellulose and chitosan solubility properties are similar to the degree that they are poorly soluble in organic solvents and water. Kurita et al have developed synthetic strategies to introduce trimethylsilyl (TMS) to the hydroxyl groups of chitomaterials with interesting results.…”
Section: Introductionmentioning
confidence: 95%